2021
DOI: 10.1158/1538-7445.sabcs20-ps12-07
|View full text |Cite
|
Sign up to set email alerts
|

Abstract PS12-07: Lenvatinib plus pembrolizumab for previously treated, advanced triple-negative breast cancer: Early results from the multicohort phase 2 LEAP-005 study

Abstract: Background: Triple-negative breast cancer (TNBC) is associated with poor survival outcomes and treatment options are limited. These tumors lack therapeutic targets and become rapidly resistant to chemotherapy. The anti–PD-1 antibody pembrolizumab showed durable antitumor activity and manageable safety in patients with TNBC in the KEYNOTE-012, KEYNOTE-086, and KEYNOTE-119 studies. The combination of lenvatinib, an antiangiogenic multiple receptor tyrosine kinase inhibitor, with pembrolizumab has shown promising… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…For instance, lenvatinib (LEN) is a multitargeted tyrosine kinase inhibitor (TKI) blocking receptors such as vascular endothelial growth factor receptors (VEGFRs) and fibroblast growth factor receptors (FGFRs), and has been approved for first-line treatment of unresectable hepatocellular carcinoma as monotherapy and first-line treatment of advanced renal cell carcinoma together with pembrolizumab. The potential efficacy of LEN on TNBC patients is also under active investigation 13 . Accumulating data suggest that LEN can inhibit immunosuppressive cells and prevent CD8 + T cell exhaustion via blocking VEGFR-mediated and FGFR-mediated pathways while directly killing cancer cells 14 , 15 .…”
Section: Introductionmentioning
confidence: 99%
“…For instance, lenvatinib (LEN) is a multitargeted tyrosine kinase inhibitor (TKI) blocking receptors such as vascular endothelial growth factor receptors (VEGFRs) and fibroblast growth factor receptors (FGFRs), and has been approved for first-line treatment of unresectable hepatocellular carcinoma as monotherapy and first-line treatment of advanced renal cell carcinoma together with pembrolizumab. The potential efficacy of LEN on TNBC patients is also under active investigation 13 . Accumulating data suggest that LEN can inhibit immunosuppressive cells and prevent CD8 + T cell exhaustion via blocking VEGFR-mediated and FGFR-mediated pathways while directly killing cancer cells 14 , 15 .…”
Section: Introductionmentioning
confidence: 99%
“…Lenvatinib, a small-molecule tyrosine kinase inhibitor that inhibits VEGFR-1 (FLT1), VEGFR-2 (KDR), and VEGFR-3 (FLT4), in combination with an immune checkpoint inhibitor, may have significant clinical activity in selective patients with heavily pretreated metastatic TNBC [218] (Figure 15). In combination with pembrolizumab, lenvatinib showed promising antitumor activity with manageable toxicity in patients with previously treated advanced TNBC [219].…”
Section: Lenvatinib (33)mentioning
confidence: 99%
“…Lenvatinib has demonstrated immune modulatory effects through reduction in tumor associated macrophages and increased type I interferon signaling [64]. The ongoing phase II LEAP-005 trial has reported preliminary efficacy of lenvatinib and pembrolizumab with an ORR of 29% in 31 patients with TNBC [65]. Specific AKT inhibitors may also contribute to favorable changes in the tumor microenvironment through reduction in regulatory T cells [66].…”
Section: Early Phase Trials Of Novel Immunotherapy Combinationsmentioning
confidence: 99%